“Trying to Grab Pieces of Hope”: Exploring the Experiences of Black and Hispanic Parents following a Congenital Heart Disease Diagnosis - Rent, Sharla; Poon, Kwai Tei Candy Chan; Sooy-Mossey, Meredith; Weeks, Mary Frances; Roberts, James C.; Douglas, Dakota; Ellestad, Sarah; Lemmon, Monica E.; Hill, Kevin; Windom, McAllister (American Journal of Perinatology Reports, 2025)
Objective Congenital heart disease (CHD) is an important contributor to pediatric morbidity and mortality. Unfortunately, disparities in the diagnosis and treatment of CHD exist across racial and ethnic groups. The objective of this study was to share the experiences of Hispanic and Black families with CHD to better understand their needs.Study Design This was a descriptive qualitative study involving two 2-part focus groups, one conducted in English and one in Spanish, consisting of parents of infants with CHD. Focus groups were audio recorded, transcribed, and analyzed via a conventional content analysis approach.Results Six family members participated, representing a range of cardiac diagnoses. Two participants cited their identity as non-Hispanic Black and four as Hispanic. Three organizing themes emerged related to (1) communication, (2) psychosocial needs and processing, and (3) practical challenges associated with having a child with CHD. Together, these organizing themes supported a singular global theme: structural and socioemotional gaps in care exist for families of infants with CHD that need to be met in order to optimize care for patients and families.Conclusion Societal and systems-level factors, including structural inequities, contribute to the care gaps experienced by racial and ethnic minority families of children with CHD.Key Points
Keywords: congenital heart disease; complex congenital heart disease; neonatal intensive care; parental mental health; communication; health disparities; health equity